Formation of silica aggregates in sorghum root endodermis is predetermined by cell wall architecture and development. (22nd June 2017) - Soukup, Milan; Martinka, Michal; Bosnić, Dragana; Čaplovičová, Mária; Elbaum, Rivka; Lux, Alexander
Abstract: Background and Aims Deposition of silica in plant cell walls improves their mechanical properties and helps plants to withstand various stress conditions. Its mechanism is still not understood and silica–cell wall interactions are elusive. The objective of this study was to investigate the effect of silica deposition on the development and structure of sorghum root endodermis and to identify the cell wall components involved in silicification. Methods Sorghum bicolor seedlings were grown hydroponically with (Si+) or without (Si−) silicon supplementation. Primary roots were used to investigate the transcription of silicon transporters by quantitative RT–PCR. Silica aggregation was induced also under in vitro conditions in detached root segments. The development and architecture of endodermal cell walls were analysed by histochemistry, microscopy and Raman spectroscopy. Water retention capability was compared between silicified and non-silicified roots. Raman spectroscopy analyses of isolated silica aggregates were also carried out. Key Results Active uptake of silicic acid is provided at the root apex, where silicon transporters Lsi1 and Lsi2 are expressed. The locations of silica aggregation are established during the development of tertiary endodermal cell walls, even in the absence of silicon. Silica aggregation takes place in non-lignified spots in the endodermal cell walls, which progressively accumulate silicic acid, and its condensation initiates at arabinoxylan–ferulic acid complexes. Silicification does not support root water retention capability; however, it decreases root growth inhibition imposed by desiccation. Conclusion A model is proposed in which the formation of silica aggregates in sorghum roots is predetermined by a modified cell wall architecture and takes place as governed by endodermal development. The interaction with silica is provided by arabinoxylan–ferulic acid complexes and interferes with further deposition of lignin. Due to contrasting hydrophobicity, silicification and lignification do not represent functionally equivalent modifications of plant cell walls.